2017
DOI: 10.1080/01576895.2016.1277361
|View full text |Cite
|
Sign up to set email alerts
|

Archival orthodoxy of post-custodial realities for digital records in South Africa

Abstract: Some public entities in South Africa have implemented digital records systems over a period of 20 years. In terms of the South African archival legal framework, there is a need for such entities to transfer the records into archival custody. However, there is consensus among researchers that there is no infrastructure to ingest digital records into archival custody in South Africa. Furthermore, some public entities have migrated from one system to another since implementation and there is a possibility that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 12 publications
1
40
0
Order By: Relevance
“…This allows NARSSA to insist that mechanisms and procedures be put in place to ensure that archival records are identified while still functional and then preserved appropriately. However, although this is reflected in the policy, in reality, this is the opposite as Ngoepe (2017) reported that, in practice, many governmental entities destroy digital records when records are no longer needed for their current needs. This is so because NARRSA and the provincial archives in South Africa do not have the necessary infrastructure to ingest digital records of enduring value into archival custody (Ngoepe, 2017).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows NARSSA to insist that mechanisms and procedures be put in place to ensure that archival records are identified while still functional and then preserved appropriately. However, although this is reflected in the policy, in reality, this is the opposite as Ngoepe (2017) reported that, in practice, many governmental entities destroy digital records when records are no longer needed for their current needs. This is so because NARRSA and the provincial archives in South Africa do not have the necessary infrastructure to ingest digital records of enduring value into archival custody (Ngoepe, 2017).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…However, although this is reflected in the policy, in reality, this is the opposite as Ngoepe (2017) reported that, in practice, many governmental entities destroy digital records when records are no longer needed for their current needs. This is so because NARRSA and the provincial archives in South Africa do not have the necessary infrastructure to ingest digital records of enduring value into archival custody (Ngoepe, 2017). Although NARSSA propagates for the earliest possible transfer into archival custody of digital records with enduring value, this is not happening as alluded to above.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Several scholars have conducted studies investigating the legislative framework guiding records management in the public sector in South Africa (Ngoepe 2017;Katuu 2016;Ngoepe 2016;Ngoepe and Saurombe 2016;Katuu and Van der Walt 2016;Ngoepe and Makhubela 2015;Ngoepe and Makhura 2008). However, these studies did not specifically focus on the application of legislative frameworks in managing medical records in Limpopo Province.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In South Africa, the responsibility of regulating government records falls under the auspices of the National Archives and Records Services (NARSSA) in the Department of Arts and Culture (DAC), which according to Ngoepe (2017) does not have the necessary infrastructure to manage and preserve digital records. As a result, digital records are left to the creating agencies to manage and preserve.…”
Section: Introduction and Background To The Problemmentioning
confidence: 99%
“…Notwithstanding the importance of cloud storage, the challenge with the current practice in the context of the South African government still remains as records are stored on the premises of each department's registries manned by untrained registry clerks. Only a few governmental bodies have automated their records management programme (Ngoepe 2017). Pickover and Harris (2001) maintained that traditional paper-based records are likely to be inefficiently provided with resources, manned by junior records practitioners with little status and subject to high turnover rates, and incorrectly connected, if at all, to a parallel or similar electronic records management system.…”
Section: Introduction and Background To The Problemmentioning
confidence: 99%